Musical Instruments of the Indigenous People of South Africa. Percival R. Kirby. 2013. (1st ed. OUP 1934, repr. 1953, 2nd ed. Witwatersrand University Press 1965), 3rd ed. Witwatersrand University Press (title updated from 'native races' ) 159 ills., map, xxxv, 400pp. - Tracey, Andrew (International Library of African Music, 2014)
pages: 146-147
Keywords: South Africa; African Music